Atomic wavelength in a kappa-distribution plasma. (July 2015) - Kar, Sabyasachi; Jiang, Zishi; Cheng, Yongjun; Ho, Y K
Synopsis: We investigate the plasmas screening effect on the transition wavelength for helium atom using correlated exponential wave functions within the framework of Ritz variational principle. Transition wavelengths are presented as functions of plasma screening parameters.